Challenges to the discourse on human rights after 50 issues of Derechos y Libertades - Barranco Avilés, María del Carmen (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The author questions the extent to which the problems that were identified as current in the first issue of Derechos y Libertades remain challenges to the human rights discourse. The conclusion she reaches is that even today it is necessary to discuss universality, participation, inequalities, the degradation of social rights, the role of rights in international relations and the environment. In addition, to the above problems are added the threat of terrorism and the response to this threat, as well as the rise of right-wind populism, and the impact of the technological revolution. Currently, a context marked by the Anthropocene, climate change and the impact of new technologies makes the discourse of rights and, above all, the extension of this beyond academic environments through education in rights, peremptory.